Multiple modes of AFM reveal distinct mechanical properties for dystrophin and utrophin not manifest by small fragments - Cailong Hua; Joseph Vavra; Jacob Powers; Joseph M. Muretta; James M. Ervasti; Murti V. Salapaka (Proceedings of the National Academy of Sciences, 2026)
Duchenne muscular dystrophy (DMD) is a lethal muscle disease caused by the absence of the protein dystrophin. Dystrophin is hypothesized to work as a molecular shock absorber that limits myofiber membrane damage when undergoing reversible unfolding upon muscle stretching and contraction. Here, we report the mechanical characterization of single full-length dystrophin (Dys) molecules using two operational modes of atomic force microscopy; constant speed and constant force as well as Monte Carlo simulations. Furthermore, we have compared Dys with large fragments encoding the N-terminus through spectrin repeat 10 (DysN-R10), the C-terminal retinal isoform of dystrophin (Dp260), and full-length utrophin (Utr). Our comprehensive data reveal that Dys, DysN-R10, and Dp260, all show a uniform, brittle unfolding behavior, whereas Utr demonstrates more complex unfolding dominated by a stiffening spring behavior. These fundamentally different mechanical behaviors in vitro suggest different in vivo functions for Dys and Utr with implications for the potential efficacy of Utr upregulation to substitute for Dys deficiency in DMD.